Lung stereotactic radiation therapy: Early results from the Salah Azaiez Institute - Mousli, Alia; Kaabia, Wael; Boudhina, Emna; Bouguerra, Fadoua; Yousfi, Amani; Ben Zid, Khedija; Ben Salem, Lotfi; Essadok, Ali; Ghorbel, Asma; Besbes, Mounir; Zarraa, Semia; Yahyaoui, Safia; et al. (La Tunisie medicale, 2024)
Introduction: Stereotactic Body Radiation Therapy (SBRT) has transformed lung cancer care, delivering precise treatment with minimal harm to healthy tissue. Aim: This study examined the experience at the Salah Azaiez Institute (SAI) in lung cancer patients. Methodology: we conducted a retrospective study on patients treated with SBRT from 2019 to 2022. Planification imaging included four-dimensional CT scans and delineation of target volumes and organs-at-risk was done as per international guidelines. Treatment doses were tailored based on tumour location. Results: A total of 10 cases were included. The male-to-female sex ratio was 4:1, with a median age of 69.5 years. Three had unconfirmed primary lung tumours, while five had inoperable stage I-IIA adenocarcinomas primarily due to compromised respiratory function. Two had oligometastatic lung diseases. All underwent recent thoracic-CT and PET-CT evaluations to exclude pulmonary fibrosis. The median lesion size was 40mm. Karnofsky’s performance status ranged from 70 to 90, with no contraindications to the supine position. Eight out of 10 patients received 8 fractions of 7.5 Gy at the 80% isodose. For that regimen, the D95%, D99%, and Dmax were respectively, 60 Gy, 56 Gy, 73 Gy. All organs-at-risk dosimetric criteria were met. Acute toxicities included worsened coughs in 2 patients and fatigue in 6. After a mean follow-up of 23 months, no rib fractures or haemoptysis were observed, and no local recurrence was reported on the last chest CT scan. Conclusion: SBRT demonstrates promise for lung cancer treatment, though challenges persist in precise targeting ....